Young pregnant women and risk for mental disorders: findings from an early pregnancy cohort. Issue 2 (March 2019) - Lockwood Estrin, Georgia; Ryan, Elizabeth G.; Trevillion, Kylee; Demilew, Jill; Bick, Debra; Pickles, Andrew; Howard, Louise Michele
Abstract : Background: Young women aged 16–24 are at high risk of common mental disorders (CMDs), but the risk during pregnancy is unclear. Aims: To compare the population prevalence of CMDs in pregnant women aged 16–24 with pregnant women ≥25 years in a representative cohort, hypothesising that younger women are at higher risk of CMDs (depression, anxiety disorders, post-traumatic stress disorder, obsessive–compulsive disorder), and that this is associated with low social support, higher rates of lifetime abuse and unemployment. Method: Analysis of cross-sectional baseline data from a cohort of 545 women (of whom 57 were aged 16–24 years), attending a South London maternity service, with recruitment stratified by endorsement of questions on low mood, interviewed with the Structured Clinical Interview DSM-IV-TR. Results: Population prevalence estimates of CMDs were 45.1% (95% CI 23.5–68.7) in young women and 15.5% (95% CI 12.0–19.8) in women ≥25, and for 'any mental disorder' 67.2% (95% CI 41.7–85.4) and 21.2% (95% CI 17.0–26.1), respectively. Young women had greater odds of having a CMD (adjusted odds ratio (aOR) = 5.8, 95% CI 1.8–18.6) and CMDs were associated with living alone (aOR = 3.0, 95% CI 1.1–8.0) and abuse (aOR = 1.5, 95% CI 0.8–2.8). Conclusions: Pregnant women between 16 and 24 years are at very high risk of mental disorders; services need to target resources for pregnant women under 25, including those in their early 20s. Interventions enhancing social networks, addressing abuse and providing adequate mental health treatment may minimise adverse outcomes for young women and their children. Declaration of interest: None.